2018
DOI: 10.1016/j.jhep.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus eradication by direct-acting antiviral agents improves carotid atherosclerosis in patients with severe liver fibrosis

Abstract: Hepatitis C virus eradication by direct-acting antiviral agents improves carotid atherosclerosis in patients with advanced fibrosis/compensated cirrhosis. The improvement in intima-media thickness and carotid thickening was confirmed after stratification for severity of liver disease and cardiovascular risk factors. Hepatitis C virus eradication by direct-acting antiviral agents also lead to improvement in glucose homeostasis and increased cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 48 publications
5
93
0
2
Order By: Relevance
“…A recent study reported a significant decrease in carotid intima-media thickness measurement in HCV-infected persons with advanced fibrosis or compensated cirrhosis who were treated with a DAA regimen, suggesting a putative mechanism of CVD risk decrease. 39 Taken together, these observations strengthen the mounting evidence of the association between advanced liver fibrosis and CVD events and a significant decrease in such risk with treatment.…”
Section: March 2019supporting
confidence: 70%
“…A recent study reported a significant decrease in carotid intima-media thickness measurement in HCV-infected persons with advanced fibrosis or compensated cirrhosis who were treated with a DAA regimen, suggesting a putative mechanism of CVD risk decrease. 39 Taken together, these observations strengthen the mounting evidence of the association between advanced liver fibrosis and CVD events and a significant decrease in such risk with treatment.…”
Section: March 2019supporting
confidence: 70%
“…However, findings regarding vascular parameters following SVR that is achieved by DAA are inconsistent. One recent study measured and compared the intima thickness of the carotid artery at baseline and that 9‐12 months after the end of treatment . It enrolled 182 DAA‐treated CHC patients and all achieved SVR.…”
Section: Chronic Hepatitis Viral Infection and Arteriosclerosismentioning
confidence: 99%
“…One recent study measured and compared the intima thickness of the carotid artery at baseline and that 9-12 months after the end of treatment. 206 It enrolled 182 DAA-treated CHC patients and all achieved SVR. The intima thickness significantly decreased (0.94 ± 0.29 mm vs 0.81 ± 0.27, P < .001) and a significant reduction in the prevalence of carotid thickening from baseline to follow-up was observed (42.8% vs 17%, P < .001).…”
Section: Chroni C Hepatitis Vir Al Infec Ti On and Arteri Oscleros Ismentioning
confidence: 99%
“…A new and very important observation of the present study is the significant association between the procoagulant imbalance and the early atherosclerotic lesions, assessed by cIMT. Several studies pointed out that HCV infected subjects have a significantly high prevalence of early atherosclerosis despite being young and having a favourable cardiovascular risk profile, which improves after virus eradication . In line with this is the observation that viral eradication by the new DAA is followed by a reduction in early atherosclerosis alterations.…”
Section: Discussionmentioning
confidence: 99%